Low Bandgap Donor-Acceptor π-Conjugated Polymers From Diarylcyclopentadienone-Fused Naphthalimides - Li, Xiaolin; Guo, Jing; Yang, Longfei; Chao, Minghao; Zheng, Liping; Ma, Zhongyun; Hu, Yuanyuan; Zhao, Yan; Chen, Huajie; Liu, Yunqi (Frontiers in Chemistry, 2019)
Two novel aromatic imides, diarylcyclopentadienone-fused naphthalimides (BCPONI-2Br and TCPONI-2Br), are designed and synthesized by condensation coupling cyclopentadienone derivatives at the lateral position of naphthalimide skeleton. It is found that BCPONI-2Br and TCPONI-2Br are highly electron-withdrawing acceptor moieties, which possess broad absorption bands and very low-lying LUMO energy levels, as low as –4.02 eV. On the basis of both building blocks, six low bandgap D-A copolymers (P1-P6) are prepared via Suziki and Stille coupling reactions. The optical and electrochemical properties of the polymers are fine-tuned by the variations of donors (carbazole, benzodithiophene, and dithienopyrrole) and π-conjugation linkers (thiophene and benzene). All polymers exhibit several attractive photophysical and electrochemical properties, i.e., broad near-infrared (NIR) absorption, deep-lying LUMO levels (between –3.88 and –3.76 eV), and very small optical band gap (Egopt) as low as 0.81 eV, which represents the first aromatic diimides-based polymer with the Egopt less than 1.0 eV. Investigation of charge carrier transport properties shows that P5 exhibits a moderately high hole mobility of 0.02 cm2 V−1 s−1 in bottom-gate field-effect transistors (FETs) and a typical ambipolar transport behavior in top-gate FETs. The findings suggest that BCPONI-2Br, TCPONI-2Br, and the other similar acceptor units are promising building blocks for novel organic semiconductors with outstanding NIR activity, high electron affinity, and low band-gap, which can be extended to various next-generation optoelectronic devices.